Integrative Islamic Personality Sebagai Prediktor Student Wellbeing Pada Siswa Pondok Pesantren - Raudatussalamah Raudatussalamah; Desma Husni; John Herwanto; Cipto Hadi; Linda Aryani; Ahmadin Ahmad Tohar (JURNAL PSIKOLOGI, 2022)
Pusat utama untuk mencapai kesuksesan siswa di sekolah dan kehidupan adalah “sense of wellbeing”. Melalui sense of wellbeing, pengembangan terhadap kepercayaan diri siswa, identitas diri yang positif, resiliensi menjadi sangat memungkinkan akan berkorelasi dengan dengan aspek yang lain. Tujuan penelitian ini untuk menguji hubungan antara Integrative Islamic Personality dengan Student Wellbeing pada Santri Pondok Pesantren. Jumlah subjek penelitian yaitu 538 santri. Instrument yang digunakan yaitu skala integrative Islamic personality dan Student wellbeing. Teknik analisa data menggunakan analisis regresi. Hipotesis dalam penelitian yaitu ada pengaruh Integrative Islamic Personality dengan Student Wellbeing diterima. Kesejahteraan siswa dapat diwujudkan melalui pengembangan kepribadian islam yang integrative. Semakin kuat individu dalam mengintergrasikan kepribadiannya dengan islam maka semakin tinggi kesejahteraan yang dirasakan.                          Key word; Integratif Islamic Personality, Student Wellbeing INTEGRATIVE ISLAMIC PERSONALITY AS A PREDICTOR OF STUDENT WELLBEING IN SANTRI PONDOK PESANTREN  Raudatussalamah, raudatussalamah@uin-suska.ac.idDesma HusniDesma.husni @uin-suska.ac.idFakultas Psikologi Universitas Islam Negeri Sultan Syarif Kasim Riau AbstractThe main center for achieving student success in school and life is "a sense of well-being". Through a sense of well-being, the development of students' self-confidence, a positive self-identity, resilience is very likely to be correlated with other aspects. The purpose of this study was to examine the relationship between Integrative Islamic Personality and Student Wellbeing at Islamic Boarding School Santri. The number of research subjects is 538 students. The instrument used is the integrative Islamic personality and student wellbeing scale. Techniques Data analysis using regression analysis. The hypothesis in this study is that there is an influence of Integrative Islamic Personality with Student Welbeing is accepted. Student welfare can be realized through the development of an integrative Islamic personality. The stronger the individual in integrating his personality with Islam, the higher the perceived wellbeing.Key word; Integrative Islamic Personality, Student Wellbeing